Why are chlorinated pollutants so difficult to degrade aerobically? Redox stress limits 1,3-dichloroprop-1-ene metabolism by Pseudomonas pavonaceae - Nikel, Pablo Ivan (2013)
Chlorinated pollutants are hardly biodegradable under oxic conditions, but they can often be metabolized by anaerobic bacteria through organohalide respiration reactions. In an attempt to identify bottlenecks limiting aerobic catabolism of 1,3-dichloroprop-1-ene (1,3-DCP; a widely used organohalide) in Pseudomonas pavonaceae, the possible physiological restrictions for this process were surveyed. Flow cytometry and a bioluminescence reporter of metabolic state revealed that cells treated with 1,3-DCP experienced an intense stress that could be traced to the endogenous production of reactive oxygen species (ROS) during the metabolism of the compound. Cells exposed to 1,3-DCP also manifested increased levels of D-glucose-6-P 1-dehydrogenase activity (G6PDH, an enzyme key to the synthesis of reduced NADPH), observed under both glycolytic and gluconeogenic growth regimes. The increase in G6PDH activity, as well as cellular hydroperoxide levels, correlated with the generation of ROS. Additionally, the high G6PDH activity was paralleled by the accumulation of D-glucose-6-P, suggesting a metabolic flux shift that favours the production of NADPH. Thus, G6PDH and its cognate substrate seem to play an important role in P. pavonaceae under redox stress caused by 1,3-DCP, probably by increasing the rate of NADPH turnover. The data suggest that oxidative stress associated with the biodegradation of 1,3-DCP reflects a significant barrier for the evolution of aerobic pathways for chlorinated compounds, thereby allowing for the emergence of anaerobic counterparts.